The modern concepts of increasing banks’ competitiveness - E. S. Bakhmetyeva (Путеводитель предпринимателя, 2020)
The most important component of bank governance is the use of existing concepts of competitiveness of banks, whose main aim is the promotion of banking services - from banking institution to the client, which leads to increased efficiency of the banking business.